The Financial History of the American Automobile Industry (Book). - Hanson, Arthur W. (The Accounting Review, 1930)
Reviews the book "The Financial History of the American Automobile Industry: A Study of the Ways in which the Leading American Producers of Automobiles Have Met Their Capital Requirements," by Lawrence H. Seltzer.